Atlas of Epilepsies - Panayiotopoulos, C. P.; SpringerLink (Online service) (London : Springer London, 2010)
Atlas of Epilepsies is a landmark, all-encompassing, illustrated reference work and hands-on guide to the diagnosis, management and treatment of epilepsy in all its forms and across all age groups. The premier text in the field with over one thousand images, the Atlas$1 (Bs highly illustrative approach tackles the difficult subject of epileptic seizures and epileptic syndromes, accompanied by sequential photographs of each management step. Intraoperative photographs are accompanied by detailed figure legends describing nuances, subtleties, and the thought processes involved in each step, providing a fuller understanding of each procedure. The Atlas draws on the expertise of over 300 internationally-renowned experts, and is liberally interspersed with clinical insights and personal vignettes that offer helpful tips, technical advice and critical knowledge to the clinician and scholar. The thorough and complete table of contents includes dedicated sections or chapters on important topics such as neonatal and pediatric seizures; imitators of epilepsy; EEG and neuroimaging; psychiatric and quality of life aspects of epilepsy; and a complete guide to treatment options including current and up-to-date chapters on pharmaceuticals, surgical procedures, and additional and alternative treatments. No other publication addresses epilepsies as thoroughly and completely as the Atlas of Epilepsies. Exhaustive and illustrative, convenient and current, this reference is sure to be the premier text on epilepsy for many years to come.s
Definitions and Classifications -- Historical Aspects -- Epidemiology -- Etiology and Pathology -- Pathophysiology -- Animal and Experimental Models of Epileptic Seizures -- Epileptogenicity in the Developing Brain -- Generalized Epileptic Seizures -- Focal Epileptic Seizures -- Reflex Epileptic Seizures -- Neonatal Seizures -- Status Epilepticus -- Imitators of Epileptic Seizures -- History, Physical and Mental Examination and Assessment. - EEG -- Neuroimaging -- Neonatal Epileptic Seizures and Neonatal Epileptic Syndromes -- Idiopathic Epileptic Seizures and Syndromes in Infancy -- Epileptic Encephalopathies in Infancy and Early Childhood -- Severe Neocortical Epileptic Syndromes in Infancy and Childhood -- Benign Childhood Focal Seizures and Related Epileptic Syndromes -- Idiopathic Generalized Epilepsies -- Familial (autosomal dominant) Focal Epilepsies -- Symptomatic and Cryptogenic Focal Epilepsies -- Reflex Seizures and Reflex Epilepsies -- Progressive Myoclonic Epilepsies -- Epilepsies in Specified Groups of Patients -- Comorbidity -- Psychiatric Aspects -- Impact of Epilepsies -- Quality of Life -- Stigma -- The Epilepsy Treatment Gap -- Legal Aspects -- Great Achievers Amongst Epilepsy Patients -- Management of Epilepsies -- AED Prophylactic Treatment -- Surgery for Epilepsies -- Additional and Alternative Treatments. - Pharmacopoeia.
Keywords: Medicine; Neurology; Medicine & Public Health; Neurology